ChemInform Abstract: Nano‐NiFe2O4 Catalyzed Microwave Assisted One‐Pot Regioselective Synthesis of Novel 2‐Alkoxyimidazo[1, 2‐a]pyridines under Aerobic Conditions. Issue 25 (June 2016) - Payra, Soumen; Saha, Arijit; Banerjee, Subhash
Abstract: starting from 2‐aminopyridine, β‐nitrostyrenes, and various alcohols